2023
DOI: 10.3390/ma16020609
|View full text |Cite
|
Sign up to set email alerts
|

Stress–Dilatancy Behaviourof Fibre-Reinforced Sand

Abstract: This paper analyses the stress–strain behaviour of fibre-reinforced sand using the results obtained by drained triaxial compression tests presented in the literature. The general stress–plastic dilatancy equation of the Frictional State Concept has been used to describe the behaviour of fibre-reinforced sand for different shear phases. The behaviour of pure sand is taken as a reference for the behaviour of sand with added fibres. It is shown that the characteristic shear phases can only be determined when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The general stress ratio-plastic dilatancy relationship using the frictional state concept (FSC) is as follows [24]:…”
Section: Stress-plastic Dilatancy Relationship For Soilsmentioning
confidence: 99%
See 3 more Smart Citations
“…The general stress ratio-plastic dilatancy relationship using the frictional state concept (FSC) is as follows [24]:…”
Section: Stress-plastic Dilatancy Relationship For Soilsmentioning
confidence: 99%
“…where 𝜙 𝑜 is the angle of friction at the critical frictional state [24,25]. The definition of critical frictional state and the calculation procedure using 𝜙 𝑜 were provided by Szypcio [24]. For conventional drained triaxial compression, 𝛿𝑞 𝛿𝑝′ ⁄ = 3, and…”
Section: Stress-plastic Dilatancy Relationship For Soilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zenon et al [21] analyzed the stress-strain characteristics of fiber-reinforced sandy soils by means of triaxial drainage compression tests and found that tensile strains had to be generated in order for the fiber reinforcement to be demonstrated.…”
Section: Introductionmentioning
confidence: 99%